Consumption growth and volatility with consumption externalities - Runli Xie (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
This paper studies the link between group-specific consumption growth and volatility within a framework of heterogeneous agents, under the assumption of a consumption externality. Household preferences are related to the volatility through asset holding decisions: volatility decreases with groups' degree of patience, and increases with household eagerness to keep up with the group average. Moreover, consumption growth is expected to relate positively to the volatility. This last hypothesis is tested using household data imputed from GSOEP and the German Income and Expenditure Survey (EVS), where a U-shaped relationship is found for the nondurable consumption. Moreover, examining the growth-inequality relationship using EVS data alone shows that it is positive for nondurable and negative for durable consumption.
Keywords: E21; D91; D31; D64; 330; consumption growth; consumption volatility; within-group inequality; GSOEP; EVS; Konsumentenverhalten; Volatilität; Konsuminterdependenz; Schätzung; Deutschland